Cascade dehydrative amination of glycerol to oxazoline. Issue 11 (23rd May 2018) - Pandya, R.; Mane, R.; Rode, C. V.
Abstract : A method for the direct conversion of bioglycerol to oxazoline was devised involving glycerol dehydration to acetol followed by its amination with aqueous ammonia. Abstract : Transformation of biomass into valuable nitrogen-containing compounds is highly desired, yet less explored. Here, we report a simple and efficient method for the direct conversion of bioglycerol to oxazoline involving glycerol dehydration to acetol followed by its amination using an aqueous solution of ammonia. For the two-step strategy a non-noble metal Cu–Zr catalyst was developed, giving a glycerol to acetol conversion of 78% followed by amination separately with 95% selectivity to oxazoline. Moreover, we have demonstrated a single-pot oxazoline synthesis using Ru/C as the most stable catalyst to achieve 95% selectivity to oxazoline without any leaching. XPS studies revealed the co-existence of multivalent Ru species in different percentages depending on the nature and structure of the support. These multivalent species (RuO2 and RuO3 ) have a synergistic effect on the activation of the carbonyl group, whereas Ru 0 is an active site for ammonia dissociation. NH3 -TPD and Py-IR spectroscopy results also suggest that the presence of relatively moderate acid sites and a higher Brønsted/Lewis acid ratio in the catalyst promote the selective production of oxazoline. The reaction pathway involves first glycerol dehydration to acetol. In the subsequent step, NH3 is dissociatively adsorbed on the catalyst surface and the imine thus formed is condensed with a second molecule of acetol to obtain oxazoline. The studied catalyst could be recycled successfully without any significant loss of catalytic activity.